Migration of fluorine during the reduction of copper slag from spent cathode carbon produces copper-iron alloys - Mingyang Li; Shiwei Zhou; Bo Li; Yonggang Wei; Hua Wang (Journal of Materials Research and Technology, 2023)
Spent cathode carbon (SCC) is a hazardous solid waste discharged from the aluminium electrolysis industry that poses a serious environmental pollution risk. In this paper, the migration transformation route and distribution ratio of fluorine during the reduction of copper slag by SCC were investigated. The results show that fluorine accounts for 57.92% of the slag phase, and the main phase is CaF2, which accounts for 41.75% of the gas phase and 0.33% of the alloy phase when reduced at 1460 °C with 10 wt% SCC for 90 min. The recoveries of reduced Cu and Fe reached 94.42% and 40.32%, respectively. After reduction by metallization, the F− leaching toxicity in the leaching slag was 38 mg/L, which is far below the regulatory limit (100 mg/L). In the process of copper slag reduction by SCC metallization, the copper and iron in the slag were effectively recovered, thus realizing the resourceful and harmless utilization of SCC. This achieves the goal of “treating waste with waste” and significantly reduces the treatment cost of SCC.